FAKTORFAKTOR YANG MEMPENGARUHI TERJADINYA GANGGUAN TIDUR PADA PENDERITA SINDROM PARKINSON - Nuke Ariyanie*, Thamrin Syamsudin**, Djadjang Suhana**, Yusuf Wibisono** (Neurona Majalah Kedokteran Neuro Sains, 2009)
BACKGROUND NON MOTOR SYMPTOMS OF PARKINSONISM SUCH AS SLEEP DISORDERS WOULD PLAY IMPORTANT ROLE IN MAINTAINING PATIENTS QUALITY OF LIFE THE PURPOSE OF THIS STUDY IS TO EVALUATE FACTORS THAT MAY INFLUENCE THE INCIDENCE OF SLEEP DISORDERS IN PATIENTS WITH PARKINSONISM